Automatic elasticity in OpenStack - Vilaça, Ricardo (2012)
Cloud computing infrastructures are the most recent ap- proach to the development and conception of computational systems. Cloud infrastructures are complex environments with various subsystems, each one with their own challenges. Cloud systems should be able to provide the following fun- damental property: elasticity. Elasticity is the ability to automatically add and remove instances according to the needs of the system. This is an requirement for pay-per-use billing models. Various open source software solutions allow companies and institutions to build their own Cloud infrastructure. How- ever, in most of these, the elasticity feature is quite imma- ture. Monitoring and timely adapting the active resources of a Cloud computing infrastructure is key to provide the elasticity required by diverse, multi tenant and pay-per-use business models. In this paper, we propose Elastack, an automated monitor- ing and adaptive system, generic enough to be applied to existing IaaS frameworks and intended to enable the elastic- ity they currently lack. Our approach offers any Cloud in- frastructure the mechanisms to implement automated mon- itoring and adaptation as well as the flexibility to go beyond these. We evaluate Elastack by integrating it with the Open- Stack and showing how easy it is to add these important features with a minimum, almost imperceptible, amount of modifications to the default installation.